The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1079/pns19830037
|View full text |Cite
|
Sign up to set email alerts
|

Fat supplementation in animal production—ruminants

Abstract: In 198 I, 204 ooo tonnes of fat were used by the UK Compound Food Industry in the production of foods for farm animals (Ministry of Agriculture, Fisheries and Food, 1982). Of this, it has been estimated that 65000 tonnes (Meggison, 1982) were used in the production of ruminant rations (mainly for the dairy cow), the remainder being used for pigs and poultry. Since approximately 5 million tonnes of food were produced for ruminants, this is an average rate of addition of 13 g/kg diet, although, of course, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Steele (1985) suggested that oil and fats exert an influence on DM consumption by physically preventing ruminal micro-organisms from gaining access to other dietary constituents or alternatively, free fatty acids released by hydrolysis may have toxic effects on some microbes, leading to altered populations within the rumen. The administration of 1.4 kg rolled rape seeds (HR) ( Table 2) per cow nonsignificantly increased the yield of milk, milk fat content (PO.05) and significantly increased daily fat production by 89 g per day similarly to the results obtained by Clapperton and Steele (1983). Strzetelski et al (1992) found a higher FCM yield among cows fed control diets without rape seeds and formaldehyde-or heat-treated rape seeds.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Steele (1985) suggested that oil and fats exert an influence on DM consumption by physically preventing ruminal micro-organisms from gaining access to other dietary constituents or alternatively, free fatty acids released by hydrolysis may have toxic effects on some microbes, leading to altered populations within the rumen. The administration of 1.4 kg rolled rape seeds (HR) ( Table 2) per cow nonsignificantly increased the yield of milk, milk fat content (PO.05) and significantly increased daily fat production by 89 g per day similarly to the results obtained by Clapperton and Steele (1983). Strzetelski et al (1992) found a higher FCM yield among cows fed control diets without rape seeds and formaldehyde-or heat-treated rape seeds.…”
Section: Resultsmentioning
confidence: 59%
“…The negative effect of fat on dry matter intake tends to increase as fat saturation decreases and as the amount of fat supplementation increases (Pantoja et al, 1996). The effect of added fat on voluntary feed intake seems to depend on the type of fat used, the way in which it is added, and the amount used (Clapperton and Steele, 1983). Steele (1985) suggested that oil and fats exert an influence on DM consumption by physically preventing ruminal micro-organisms from gaining access to other dietary constituents or alternatively, free fatty acids released by hydrolysis may have toxic effects on some microbes, leading to altered populations within the rumen.…”
Section: Resultsmentioning
confidence: 99%
“…High-fat diets can decrease feed intake in cattle (Clapperton and Steele, 1983). Steers, but not bulls, fed EC and GC had slightly reduced feed intakes.…”
Section: Animal Performancementioning
confidence: 92%
“…It is widely recognized that the high energy density of fats offers advantages when formulating rations for dairy cows, but in practice the average amount of fat added to dairy cake is very small -only ~ 13 g/kg in the UK (Clapperton & Steele, 1983). To some extent this reluctance to use fats is due to mechanical difficulties in cubing, but there are more fundamental objections to their inclusion.…”
mentioning
confidence: 99%